Historical Evolution, Financing And The Changing Nature Of Corporate Governance In China’s Collective Township And Village Enterprises - Smyth, Russell (Asian Academy of Management (AAM), 2001)
Collective township and village enterprises (CTVEs) have been the driving force behind China’s high rate of economic growth over a sustained period. The objective of this article is to offer one possible explanation for the emergence of new governance structures in China’s CTVE sector. The article begins by examining three specific aspects of the development of CTVEs; namely, their history, financing arrangements and changing corporate governance arrangements. After this review, it is then argued that local governments have adopted indirect forms of governance over CTVEs in response to increasing monitoring costs as firms have grown in size, while retaining direct control over the most profitable firms. However, as local governments still control most of the more successful CTVEs, as well as the resources on which private firms depend, it would be wrong to conclude that China's small and medium non-state sector is “ going private” .